Characteristics of chitosan from Penaeus monodon on chitosan-gelatin suspension viscosity - Prananingrum, Widyasri; Setiawan, Grace Caroline; Putri, Vindya Meinda; Wahyuning, Baiq Nadia Risna; Rahmitasari, Fitria; Sularsih, Sularsih; Ramadhania, Nurina Rizka; Fatmawati, Sri (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Chitosan synthesized from Penaeus monodon shells was developed into a chitosan-gelatin suspension as an injectable bone substitute for socket preservation. Purpose: To investigate the characteristics of chitosan from P. monodon shells and their influence on the viscosity of a chitosan-gelatin suspension. Methods: P. monodon shells from Tarakan Waters were prepared using three methods: Group 1) deproteinization-depigmentation-deacetylation, Group 2) demineralization-depigmentation-deacetylation, and Group 3) deproteinization-demineralization-depigmentation-deacetylation. The chitosan was characterized by morphology, moisture and ash content, molecular weight (MW), deacetylation degree (DD), and viscosity. This chitosan was made into a chitosan-gelatin suspension with a ratio of 45:55 (w/w%) (95 ml:110 ml). The differences in viscosity of the chitosan-gelatin suspension were determined using Kruskal–Wallis and Mann–Whitney tests. The effects of the chitosan’s MW and DD on the viscosity of the chitosan-gelatin suspension were analyzed using Spearman’s correlation. Results: Group 2 had the highest moisture content (10.63%), MW (159.68 kDa), viscosity of the chitosan powder (5.53 dPa.s), and viscosity of the chitosan-gelatin suspension (40.20 cps). Group 1 had the highest ash content (27.83%) and DD (93.72%). Group 3 showed the lowest ash content (1.06%), MW (37.12 kDa), and DD (86.22%), but it had good viscosity of the chitosan-gelatin suspension (37.25 cps). A significant difference in viscosity was found between the chitosan-gelatin suspension groups. Spearman’s correlation coefficients between the viscosity of the chitosan-gelatin suspension and MW and between the viscosity of the chitosan-gelatin suspension and DD were 0.389 and −0.195, respectively. Conclusion: The viscosity of a chitosan-gelatin suspension is influenced by the MW and DD of the chitosan powder. Chitosan from P. monodon can potentially be an injectable bone substitute in socket preservation.